Active tuberculosis identification based on workers environmental sanitation during the COVID-19 pandemic - Irfani, Tri Hari; Fitri, Agita Diora; Roflin, Eddy; Siburian, Reynold; Umar, Tungki Pratama (YCAB Publisher & IAKMI SULTRA, 2021)
Background: Coronavirus Disease 2019 (COVID-19) is a pandemic that may complicate the active detection of Tuberculosis (TB) and increase the mortality rate. This pushes for more effective and efficient case finding to mitigate the possible growing number of TB mortality.Objective: The purpose of this research was to identify TB among workers and to analyze the correlation between human, environmental, behavioral, and economic factors with TB findings among workers during the COVID-19 period.Methods: This research employed a case-control method conducted from January to December 2020. In total, 120 employees were included in this research. The employees were divided into two groups, sixty workers were involved in the TB case group, and another sixty workers were in the control group. We reported TB patients from several Public Health Center (Puskesmas) in each regency of South Sumatera, Indonesia. Sputum testing was performed by the rapid molecular tests (GeneXpert) and Ziehl-Neelsen to confirm the diagnosis of TB infection. We performed a Chi-square analysis to analyze factors that can influence TB cases.Results: In comparison to the control group, we found the association of age, body mass index, occupation, and sun exposure to the incidence of active TB cases (p<0.05).Conclusion: Since statistically significant differences between the two groups have been identified, the incidence of TB in workers might be affected by age, occupation, BMI, and exposure to sunlight. Associated significant variables can be integrated into the TB control program for better case-finding practice to recognize concealed burdens of TB that are overlooked due to COVID-19. This research was funded by Sainteks Sriwijaya University 2020.